Measuring Academic Resilience through Psychological Well-being and Decision-Making Ability Among Economics Education Students in the Society 5.0 Era - Devangga Putra Adhitya Pratama; Novita Aprilia; Meyla Winka Putri; Natthaphol Nitichotchaisiri (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
Abstract: The increasing complexity of learning in the Society 5.0 era has heightened the risk of academic stress, which impacts students’ ability to maintain consistent academic performance. This study aims to analyze the influence of psychological well-being and decision-making ability on the academic resilience of Economics Education students. An explanatory research design was used, involving 241 students selected through proportionate random sampling. Data were collected using Ryff’s Psychological Well-Being Scale to measure psychological well-being, the Decision-Making Ability Scale to measure decision-making ability, and the Academic Resilience Scale to measure students’ academic resilience, which were analyzed using multiple linear regression. The results indicate that psychological well-being and decision-making ability have a positive and significant influence, accounting for 68.4% of the variation in students’ academic resilience. This study establishes a correlation that views academic resilience as the result of the interaction between psychological well-being and decision-making ability. The novelty of this study lies in the finding that decision-making ability plays a more dominant role than psychological well-being in shaping the academic resilience of Economics Education students. Thus, this novelty offers the perspective that enhancing psychological well-being and decision-making skills are key strategies for improving students’ academic resilience in facing the challenges of higher education in the Society 5.0 era.Abstrak: Meningkatnya kompleksitas pembelajaran pada era Society 5.0 telah memperbesar risiko tekanan akademik yang berdampak pada kemampuan mahasiswa dalam mempertahankan performa belajar secara berkelanjutan. Penelitian ini bertujuan untuk menganalisis pengaruh kesejahteraan psikologis dan kemampuan pengambilan keputusan terhadap ketahanan akademik mahasiswa Pendidikan Ekonomi. Penggunaan desain explanatory research dengan melibatkan 241 mahasiswa melalui penentuan proportionate random sampling. Data dikumpulkan menggunakan Instrumen Ryff's Psychological Well-Being Scale untuk mengukur Psychological Well-Being, Decision-Making Ability Scale untuk mengukur kemampuan pengambilan keputusan, serta Academic Resilience Scale untuk mengukur tingkat academic resilience mahasiswa yang dianalisis dengan teknik regresi linier berganda. Hasil penelitian dari kesejahteraan psikologis dan kemampuan pengambilan keputusan berpengaruh positif dan signifikan dengan mampu mewakili 68,4% variasi ketahanan akademik mahasiswa. Penelitian ini mengembangkan korelasi yang memandang ketahanan akademik sebagai hasil interaksi antara psychological well-being dan decision-making ability. Kebaruan penelitian terletak pada temuan bahwa kemampuan pengambilan keputusan memiliki peran yang lebih dominan dibandingkan kesejahteraan psikologis dalam membentuk academic resilience mahasiswa Pendidikan Ekonomi. Sehingga novelty memberikan perspektif bahwa penguatan kesejahteraan psikologis dan kemampuan pengambilan keputusan merupakan strategi penting untuk meningkatkan ketahanan akademik mahasiswa dalam menghadapi tantangan pendidikan tinggi pada era Society 5.0.